Reflective practice on lesson planning among EFL teacher educators - Amalia, Lulu Laela; Widiati, Utami; Basthomi, Yazid; Cahyono, Bambang Yudi (Universitas Pendidikan Indonesia, 2020)
As an important part of teacher professional development, a reflective practice started to flourish in the 1980s. Along with it, many scholars have researched reflective practice in various fields, one of which is English Language Teaching. The present study explores reflective practice by teacher educators in a doctoral program, focusing on how they reflect on the journey of planning their lessons ranging from their earliest teaching years up to their future hope. Narrative inquiry with a multiple case study design is employed in this study. The data in this study, which included both narrative and non-narrative data, are collected by using narrative frames and interviews. The data are then coded and analyzed using thematic analysis. The results of the study show how learning from experience in lesson planning helps teacher educators improve their teaching performance.